Analisis Kesulitan Belajar Tema Pertumbuhan dan Perkembangan Makhluk Hidup Pada Peserta Didik Kelas III - Juniar Astrid Dewanti; Fine Reffiane; Khusnul Fajriyah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
Learning difficulties are an obstacle in one or more of the psychological processes which include understanding and using language, terms and writing. This study aims to analyze the difficulties of learning mathematics, the integration of science and Indonesian as well as to identify the factors of learning difficulties in mathematics, integration of science and Indonesian. Theme 1 is the growth and development of living things. In this study using a qualitative approach, and getting the results that students who have difficulty with mathematics, science and Indonesian integration are due to not understanding the method of counting, not being able to memorize and understand the material, being less thorough and having difficulty determining what is asked in the text. story telling.. The main factors that affect students' learning difficulties are not liking the material, feeling bored easily during learning and students who do not study the material first before solving the problem.